Development of E-Module for Automation of Public Relations and Protocol Management using Articulate Storyline 3 - Risna DewiNur Haliza; Novi Trisnawati (Universitas Negeri Surabaya, 2023)
Education is a learning process that produces intelligent and educated individuals. The learning process is supported by lesson plans, media, and teaching materials. The development of teaching materials for E-Modules based on Articulate Storyline 3 is motivated by the limited ability of students to comprehend learning materials used in the form of printed books in Public Relations and Protocol subjects in class XII automation of office administration at state vocational high school 2 Buduran Sidoarjo, so that development is needed to support the learning process and make it easier for students to understand the material. This study aims to determine the feasibility of e-module teaching materials based on Articulate Storyline 3. It can be applied as teaching materials for class XII students in Public Relations and Protocol subjects. This development research uses the ADDIE development model, but is modified into Four (4) stages, namely: 1) Analysis, 2) Design, 3) Development, and (4) Implementation. Based on the results of the material expert validation, the Articulate Storyline 3-based Public Relations e-module obtained a score of 67 which was included in the